Formulasi Strategi Di Dalam Rekrutmen Anggota Baru (Pada Komite Nasional Pemuda Indonesia Banjarbaru) - Faisal Abdillah; Hadi Sunaryo; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine the recruitment strategy for new members at the KNPI Banjarbaru using a SWOT analysis. By using the KNPI Banjarbaru as an object of research carried out in  August 2020 to February 2021. The results of this study indicate that the internal and external factors of the KNPI Banjarbaru are located in quadrant I on the SWOT diagram so that a combined strategy of internal factors (Strength) and external factors (Opportunity) is needed. The SO strategy was made based on the results of interviews from the chairman of the KNPI and the Cadre Division of KNPI members in Banjarbaru which aims to take advantage of all strengths to achieve the opportunities that the KNPI members have. Keywords: SWOT analysis, recruitment strategy for new members, KNPI Banjarbaru